The Effect of Ownership, Expense Ratio, Capital Ratio and Liquidity on Financial Performance Commercial Banks (Study on Issuers on IDX) - Andarwati Andarwati (AIBPM Publisher, 2022)
ABSTRACTThe purpose of this study is to analyze the influence between Ownership, Expense Ratio, Capital Ratio and Liquidity On Financial Performance of Commercial Banks. Method. The technique used for sampling in this study was purposive sampling, with a total sample of 15 companies.The analytical method used to answer research problems and test hypotheses is a multiple regression analysis technique using SPPS. The results of this study show 1) bank ownership, the assets to loan ratio has a significant positive effect on the performance of public banks, 2) the cost of funds, deposit risk ratio, banking ratio has a significant negative effect on the performance of commercial banks, 3) the acid test ratio has no effect on performance of commercial banks. Keywords: Capital Ratio, Expense Ratio, Financial Performance, Liquidity, Ownership.